From hand tools to mechanization: characterizing gaps and opportunities for maize, bean, and coffee smallholders in Honduras - Patiño-Espejel, Joshua Esaú; Cabrera Meraz, Jeimy; Vásquez, Emil; Lopez Gomez, Jesús Antonio; Leal González, Abel Jaime; McLean-Rodríguez, Francis Denisse; Sanders, Arie; Odjo, Sylvanus; Van Loon, Jelle (CABI, 2026)
This study characterized agricultural mechanization and identified the main challenges and opportunities for maize, bean and coffee production systems across five departments in Honduras: Lempira, Copán, Intibucá, Olancho and El Paraíso. A total of 112 surveys were conducted, and four focus groups were held among farmers. The surveys gathered information on production systems and types of tools used, while focus groups explored perceptions of farmers about the challenges and mechanization needs. The farmers surveyed grow maize (95.5%), bean (92.9%), and coffee (38.4%), on areas smaller than 1 ha for maize and bean (73%) and from 1 to 5 ha for coffee (51.2%), located on hillsides, plains, and mixed terrain. The use of motorized tools varied greatly between sites and crops (0-65.1%), while the use of hand tools was reported by almost all respondents (90.7 95.2%). Overall, the tools present in all sites and crops were found to be manual, such as machetes (almost 100%) and hoes (50-100%), planting sticks for corn and bean (65%), and post hole diggers for coffee (81.4%). Lowest levels of mechanization occurred in harvesting and post-harvesting, although some machinery for post-harvest coffee processing was present. In western departments, maize shelling and bean threshing are mainly performed manually (up to 90.9%), while in eastern departments a higher usage of mechanical threshers/shellers was observed (up to 85%). The major challenges for production systems reported are the labor shortage, high equipment costs, lack of financing mechanisms, and the need for mechanization solutions adapted to local conditions. The findings suggest that an efficient transformation of production systems in these regions demands scale-appropriate mechanized solutions, paired with strategies that enable a transition from entirely manual tools to small equipment that reduces physical effort of farmers.